(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Efficient and rational use of water resources in agriculture is one of the most pressing issues today. Traditional sprinkler irrigation machines result in significant water losses due to evaporation and wind influence. This article proposes a new design based on drum-hose sprinkler machines, adapted specifically for furrow irrigation. The proposed device delivers water directly to the plant root zone without spraying it into the air, thereby preventing losses caused by evaporation and wind. The design, operating principle, and efficiency of the furrow irrigation machine are analyzed and compared with traditional sprinkler machines. Based on calculations and tabular analysis, it has been shown that water savings of 20% or more can be achieved with furrow irrigation.